Knowledge and awareness of colorectal cancer (CRC) among nursing students in Puncak Alam / Sofee Md Akhlak, Azieana Dusin and Mayvelyne Mayor - Md Akhlak, Sofee; Dusin, Azieana; Mayor, Mayvelyne (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Colorectal cancer (CRC) is the second leading cancer in Malaysia. Lack of knowledge and awareness of CRC causing the burden to increase over time. A cross-sectional study was conducted to determine the level of knowledge and awareness of CRC and its relationship with sociodemographic data among nursing students at UiTM Puncak Alam. Total 136 nursing students were selected. Adapted questionnaire from previous studies was distributes to students. The Statistical Package for Social Sciences (SPSS) version 25 was used to analyzed the data which the frequency and percentage for the level of knowledge and awareness of CRC while Chi-square and Fisher's Exact test for the relationship respectively. Overall, nursing students at Puncak Alam has good knowledge and awareness of CRC. There is a significant relationship between the levels of knowledge of CRC with age (p=0.007) and year of education (p=<0.001) but conversely with awareness. The knowledge of screening types and age to start the screening of CRC were also not up to mark as this may be due to the informations related to CRC screening guidelines that have not yet been made public. Strategies on increasing knowledge about CRC's screening should be implemented and research in multi-racial nursing students recommended.